2018
DOI: 10.3390/plants8010003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth Regulators and Gelling Agents on Ex Vitro Rooting of Raspberry

Abstract: Successful acclimatization and ex vitro rooting are among the key factors reducing the cost of micropropagated plants. We compared the survival of seven Russian cultivars of raspberry (Rubus idaeus) after rooting in vitro and ex vitro. Rooted shoots adapted to nonsterile conditions much better than nonrooted ones, with survival rates of 81%–98% versus 43%–76%, respectively. We studied the effects of different combinations of plant-growth regulators and gelling agents added to a proliferation medium on ex vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 40 publications
2
10
0
1
Order By: Relevance
“…This result could be explained by the rising proportion of plantlets showing hyperhydricity symptoms during the eight-week exposure to Al, which reached about 30% in the presence of a concentration of 1 mM AlCl 3 . Usually, the hyperhydricity of in vitro-cultured plantlets is due to several factors such as the composition of culture medium, notably the concentration of phytohormones [39] and the type of gelling agent [40]. Van den Dries et al [41] proposed that hyperhydricity is caused by a water logging of the apoplast, leading to an impairment of gas exchanges.…”
Section: Discussionmentioning
confidence: 99%
“…This result could be explained by the rising proportion of plantlets showing hyperhydricity symptoms during the eight-week exposure to Al, which reached about 30% in the presence of a concentration of 1 mM AlCl 3 . Usually, the hyperhydricity of in vitro-cultured plantlets is due to several factors such as the composition of culture medium, notably the concentration of phytohormones [39] and the type of gelling agent [40]. Van den Dries et al [41] proposed that hyperhydricity is caused by a water logging of the apoplast, leading to an impairment of gas exchanges.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the plantlets developed through the ex vitro rooting method, similar to the natural root system of S. grosvenorii, had lateral roots without any callus at the base of microcuttings, making the ex vitro rooting method more suitable than the in vitro development of roots. Lebedev et al (2019) reported that ex vitro rooting of raspberry could reduce the cost and labor intensity of plant micropropagation. Unrooted microshoots of the primocane-fruiting raspberry cultivar ' Atlant' were simultaneously rooted and acclimatized in the greenhouse with a survival rate of up to 97.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Ex vitro rooting is not only advantageous for the acclimatization of plantlets, but also for the reduction of labor and costs of micropropagation (Annapurna & Rathore, 2010;Benmahioul et al, 2012;Huang et al, 2011;Phulwaria, Rai, Harish, et al, 2012;Phulwaria et al, 2011;. Successful ex vitro rooting has been applied in the micropropagation of various plant species, including blueberries (Vaccinium corymbosum L. and Vaccinium angustifolium × corymbosum) (Isutsa & Pritts, 1994), raspberries (Rubus idaeus L.) (Lebedev et al, 2019), pistacia (Pistacia vera L.) (Benmahioul et al, 2012), and other ornamental and medicinal species (Annapurna & Rathore, 2010;Huang et al, 2011;Phulwaria, Rai, Harish, et al, 2012;Phulwaria et al, 2011;Podwyszynska & Gabryszewska, 2003;Yan et al, 2010). Reports on the simultaneous rooting and acclimatization of Pyrus species on different substrates are scarce and show little success.…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment, 2iP and TDZ caused the vitrification of axillary shoots. Therefore, it is important to select a proper concentration of cytokinin, because high concentrations cause vitrification and somaclonal variations [27]. Cytokinins (BA, 2iP, and TDZ) had multifunction in the physiological processes and the development of the plant as cell division and enlargement and stimulation of protein synthesis and enzyme activity [28].…”
Section: Discussionmentioning
confidence: 99%